Evidencing the association between swimming capacities and performance indicators in water polo: a multiple regression study - Kontic, D.; Zenic, N.; Uljevic, O.; Sekulic, D.; Lesnik, B. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: Swimming capacities are hypothesized to be important determinants of water polo performance but there is an evident lack of studies examining different swimming capacities in relation to specific offensive and defensive performance variables in this sport. The aim of this study was to determine the relationship between five swimming capacities and six performance determinants in water polo.